Musculoskeletal Radiology in the Middle East: Training Programs, Current Practice, and Future Directions - Alkhayat, Abdullah; Ashkanani, Ali (Seminars in Musculoskeletal Radiology, 2018)
This article outlines the development of radiology training in the Middle East. It discusses the history of radiology in the region and current available pathways to subspecialize in musculoskeletal (MSK) radiology. Owing to the rapidly changing demographics and health indicators in the region, a major shift has occurred in the government's focus in directing more resources to advance the health care system. This in addition to intraregional initiatives, such as the establishment of many radiologic societies, has provided strong incentives toward developing radiology training programs in the region. There are profound differences in the region regarding the development of radiology, with only few countries offering structured radiology training programs and MSK radiology fellowships. To keep up with the explosion of information in imaging technology and hold clinical ground, current and future MSK radiologists must overcome certain challenges and change their approach to stay clinically relevant.
Keywords: Middle East; radiology training programs; musculoskeletal radiology